Policy Evaluation Of The Pagar Dewa Village Head Of Ondok Kelapa District, Bengkulu Central District In The Use Of Village Funds In 2020 - Mirwansyah Mirwansyah; Asnawati Asnawati; Antonio Imanda; Bando Amin C. Kader (Penerbit Jurnal Indonesia, 2022)
This study aims to determine the